Prevalence of Impacted Third Molar Teeth among Andhra Population in Bhimavaram, India – A Retrospective study of 4 Years - Syed Kamran , Bokhari (International Journal of Psychosocial Rehabilitation, 2014)
An impacted tooth is one that cannot, or will not erupt into its normal occlusal position, and is therefore pathologic and requires treatment. Missing teeth and teeth not erupting into its desirable position is a routine phenomenon for dentists and distressing phenomenon for patients. An impacted tooth is prone to cause distal caries of second molar in some cases depending upon the angulation of impacted tooth. Tooth impacted also cause pain, food lodgment, gum swelling, formation of cysts by enlargement of follicular space. As such, it is advisable to extract the impacted tooth at the earliest. Considerable debate exists in the literature regarding prophylactic removal of impacted third molar teeth.